Association of Pectolytic Fluorescent PSeudomonas with Postharvest Rots of Onion - El-Hendawy, H.H. (Phytopathologia Mediterranea, 2004)
Five isolates of pectolytic fluorescent pseudomonads were obtained from a rotted onion bulb and identifiedas Pseudomonas marginalis. At both 4 and 25oC, all isolates caused soft rot to detached plant parts of onion andto carrot, celery, cucumber, pepper, spinach, tomato and turnip (but not garlic). They did not however cause anysymptoms in living plants of these same species. These results suggest that the onion isolates are a postharvestpathogen which is not destructive in the field but becomes a threat to fresh vegetables stored at low-temperature.Analysis of cellulosolytic and pectic enzymes revealed that pectic lyases, but not polygalacturonases, pectin methylesterases and cellulases were produced in culture by each isolate.